Associations of oral health status and swallowing function with cognitive impairment in the aging population: a cross-sectional study - Yong Chen; Canyang Li; Yongmei Fan; Lili Jiao; Matthew Silverman; Masashi Ishimaru; Jing Wang; Alice J. Van Pelt; Rumi Wang (BMC, 2023)
Abstract Background The purpose of this study was to investigate the relationships of oral health status and swallowing function with cognitive impairment in community-dwelling older adults from Changsha, Hunan Province, China. Methods In this cross-sectional study, we analyzed the data of 215 participants aged ≥ 50 years which were retrieved from the Xiangya and Panasonic mild cognitive impairment (MCI) Study, a community-based study conducted among the residents of the urban areas of Hunan province in China. Demographic information of all participants was collected. We determined oral function by evaluating oral hygiene, oral dryness, occlusal force, tongue pressure, chewing function, swallowing function, remaining teeth number, and other indicators. The mini-mental state examination (MMSE) was used to screen for cognitive function. The relationship between each oral function evaluation item and cognitive function was investigated using correlation analysis. The associations between oral health status and swallowing function with cognitive impairment were inferred using multiple regression analysis. Results The general characteristics of participants showed statistically significant correlation coefficients in number of teeth remaining (p = 0.003) and number of teeth lost (p < 0.0001). Almost half of the 25 participants (48%) were aged from 70-80 years. Only 25 older adults (11.6% of the participants) were determined to have cognitive impairment by MMSE sores less than 24. Tongue pressure in male participants was the only significant independent variable that was associated with cognitive impairment (p = 0.01971). The results indicate that male participants with lower MMSE scores had a relative deficiency in tongue pressure. Conclusions In this cross-sectional study, the oral health status and swallowing function of participants were in relatively good condition and showed low correlations with cognitive impairment. However, lower tongue pressures were associated with lower MMSE scores in males, indicating it could serve as a novel oral function index for evaluating cognitive impairment.